THE INTERSECTION OF TWO EXEGETICAL TYPES OF THE QURAN - Hidayatulloh, Miftah Khilmi; Nahar, Muhammad Hasnan (Universitas Ahmad Dahlan, 2020)
The research affirmed the intersection of two exegetical types of The Quran. This study also confirmed the existence of the pure Al-tafs?r bi al-ma?th?r and the pure Al-tafs?r bi al-ra?yi. The researchers also presented the character of each type to clarify the difference between these exegetical types. The subject of this research was the exegesis, while the object of research is Al-tafs?r bi al-ma?th?r (tradition-based exegesis), Al-tafs?r bi al-ra?yi (reason-based exegesis) and the intersection between the two exegetical types. In the first step, the researchers explained Al-tafs?r bi al-ma?th?r and Al-tafs?r bi al-ra?yi, then analyzed the scope critically. The researchers compared two exegetical types of the Quran to find the differences and the intersections. The researchers also presented examples of each type of exegesis to sharpen the analysis.